Inventorizing the modern benthic foraminiferal assemblage from marginal marine environments across the North West coast of Bay of Bengal - Sen, Areen; Saha, Ratul; Sivakumar, Kuppuswamy; Bhadury, Punyasloke (Zootaxa, 2018)
Modern benthic foraminiferal assemblages are instrumental in providing information regarding changes in relative sea level as well as prevailing environmental conditions in marine environments. Marginal marine environments are coastal environments that are in most cases characterized by high influx of terrestrially originated nutrients. Inventorizing of modern benthic foraminiferal assemblages from such habitats can act as biotic indicators of water quality variations along with any changes in relative sea level. The present study documents the modern benthic foraminiferal assemblage from three major marginal marine habitats located along the North West coast of Bay of Bengal, in the Indian Ocean. Sediment samples for the purpose were thus collected from the Indian Sundarbans Delta, Chilika lagoon and the Gautami Godavari estuarine zone which encompasses the Kakinada bay. A total of 32 species of benthic foraminifera were documented during the study. The present observations were compared with previous reports of benthic foraminiferal diversity from these habitats and exhibited variability.